Pott’s Spine with Tubercular Meningitis and Primary Optic Atrophy: An Enigma with a Rare Cautionary Tale - Khursheed Alam Khan; Kunj Bihari Saraswat; Tushar Marbate; Ashok Gupta (Indian Journal of Neurosurgery)
Tuberculosis of spine, known as Pott’s spine, is a significant health risk. Misdiagnosis or delayed diagnosis with lack of timely interventions lead to serious neurological complications and is associated with morbidity and mortality. We present a case of Pott’s spine who developed tubercular meningitis with decreased vision due to primary optic atrophy, to highlight the significance of thorough clinical and neuroradiological workup with instillation of prompt antitubercular therapy in patients of central nervous system tuberculosis (CNS TB). This association of Pott’s spine with decreased vision secondary to primary optic atrophy due to tubercular involvement of the second cranial nerve is very rare. Here, associated risk factors, varied clinical presentations, complications, and treatment of CNS TB are reviewed.